A RIGHTS-BASED APPROACH TO EMPOWERING THE REMOTE INDIGENOUS COMMUNITY OF THE YAUR TRIBE - Nurwahyuliningsih, Eka; Wahyudin, Urip; Siringoringo, Rotua (Politeknik Kesejahteraan Sosial (Poltekesos) Bandung, 2025)
This study aims to examine the relevance of the Rights-Based Approach (RBA) in empowering Remote Indigenous Communities (KAT), with a focus on the Yaur Tribe in Central Papua, through an analysis of its relationship with the fulfillment of the ten basic rights of indigenous peoples. The research method used is a literature study with a systematic literature review approach to 15 national and international articles discussing KAT empowerment, rights-based approaches, and indigenous peoples' issues. Data were analyzed thematically to identify patterns of empowerment approaches, RBA principles, and their level of relevance in the social, cultural, and geographical context of the Yaur Tribe. The results of the study indicate that KAT empowerment practices in Indonesia still predominantly position indigenous peoples as objects of development. In contrast, global literature emphasizes the urgency of implementing RBA which positions indigenous peoples as rights holders and the state as duty bearers. The integration of the 5P empowerment approach with RBA principles through the PANE, PANEL, and PANTHER frameworks is considered relevant and strategic to encourage the fulfillment of the ten basic rights of the Yaur Tribe in a more just, participatory, and sustainable manner. Based on these findings, this study recommends that the formulation and implementation of KAT empowerment programs be carried out in a participatory, contextual manner, and based on the recognition of the collective rights of indigenous communities, as a prerequisite for the realization of inclusive, equitable, and sustainable development.